The Saberes Escolares Polyhedron - Marín Díaz, Dora Lilia; Parra León, Gustavo Adolfo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article offers an analytical outlook of the ‘saber escolar’1 notion through elements provided by the pedagogical practice notion, understood as a governance practice, according to the approach suggested by Michel Foucault in his courses in the Collège of France between 1978 and 1984. This perspective arises from reflections and results derived of a research entitled ‘Construcción de saberes en la escuela’, conducted in IDEP, Instituto para la Investigación Educativa y el Desarrollo Pedagógico (Institute for educational research and pedagogical development) between 2013 and 2014. Based on a description of the constitution of pedagogy in the modernity and a characterization of studies on ‘saber escolar’1, a reading method of these works through an intelligibility polyhedron is proposed. Its faces are associated with epistemologization, ethisation, politicization, esthetization thresholds. As an analytical tool, this ‘saber escolar’ polyhedron allows the exploration of a possible field of study and a positioning in front of some ways of contemporary pedagogical government, related to the emphasis on learning.